Novel dual action anti-neoplastic drugs - Meyer, Elazar (Technium BioChemMed, 2022)
A novel drug structure (a Markush structure) is presented including molecules that can be effective as dual action drugs namely as inhibitors of epidermal growth factor kinase domain as well as having anti-angiogenic activity. The novel Markush structure includes molecules that might have dual anti-neoplastic activity leading to the development of a novel effective cancer drug for treating e.g., pancreatic cancer.